2016
DOI: 10.1111/bjh.13967
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of renal function progression in adults with homozygous sickle cell disease

Abstract: Longitudinal studies of renal function may improve understanding of the pathophysiological mechanisms underlying sickle cell disease (SCD) nephropathy and may identify possible biological and clinical markers of renal function determined over time. Data from the Jamaica Sickle Cell Cohort Study (JSCCS) were extracted and the glomerular filtration rate (GFR) was estimated using the Chronic Kidney Disease Epidemiological and the SCD specific JSCCS-GFR equations from all adulthood serum creatinine measurements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
4
24
3
Order By: Relevance
“…Interestingly, in patients with SCA, macroalbuminuria and renal insufficiency appear to be associated with resistance to developing hypertension [36] Furthermore, a recent multi-center study of SCD has suggested that pulse pressure, rather than mean arterial pressure, may be more predictive of SCD-related vasculopathy, including in the kidney [50]. Nonetheless, arterial hypertension may be a risk factor for CKD in SCD [51]. For example, nocturnal hypertension, based on age-specific criteria, was associated with a lower mean eGFR in a pediatric cohort of patients with SCA and relative systemic hypertension >120/70 mmHg appears to associate with higher creatinine levels in SCA adults [52,53].…”
Section: Modifying Factorsmentioning
confidence: 99%
“…Interestingly, in patients with SCA, macroalbuminuria and renal insufficiency appear to be associated with resistance to developing hypertension [36] Furthermore, a recent multi-center study of SCD has suggested that pulse pressure, rather than mean arterial pressure, may be more predictive of SCD-related vasculopathy, including in the kidney [50]. Nonetheless, arterial hypertension may be a risk factor for CKD in SCD [51]. For example, nocturnal hypertension, based on age-specific criteria, was associated with a lower mean eGFR in a pediatric cohort of patients with SCA and relative systemic hypertension >120/70 mmHg appears to associate with higher creatinine levels in SCA adults [52,53].…”
Section: Modifying Factorsmentioning
confidence: 99%
“…A more recent study demonstrated that, after a mean follow-up of 5 years, the frequency of CKD had increased to 41.8%, and multivariate analysis identified baseline albuminuria levels and each 1-mmHg increase in systolic blood pressure as key risk factors for subsequent CKD development [14]. The close relationship between the decline in GFR and the increase in albuminuria was recently confirmed in the Jamaica Sickle Cell Cohort Study, which assessed longitudinal changes in GFR over time in individuals with homozygous SCD [15]. In a retrospective study, nephrotic syndrome, which affected 4% of SCD patients, was found to be associated with poor renal survival [16].…”
Section: Sickle Cell Nephropathy: a Global Emerging Renal Diseasementioning
confidence: 99%
“…Glomerular filtration rate progressively declines with age, with an annual rate of decline of kidney function of 1·27 ± 1·97 ml/min/1·73 m 2 reported in African‐American adults (Young et al , ). Multiple previous studies suggest that kidney function progressively declines in SCD (Gosmanova et al , ; Asnani et al , ; van Tuijn et al , ; Xu et al , ; Derebail et al , ). In a 25‐year prospective longitudinal demographic and clinical cohort study, 31 out of 725 patients with HbSS (4·2%) and 5 out of 209 patients with HbSC disease (2·4%) developed chronic renal failure (Powars et al , ).…”
Section: Discussionmentioning
confidence: 94%
“…Albuminuria is the most frequently assessed marker of kidney damage in clinical practice and occurs in up to 68% of adult patients with SCD (Ataga et al , ). Although the natural history of CKD in patients with SCD remains inadequately defined, multiple studies suggest that kidney function declines at a more rapid rate in SCD than in healthy individuals (Asnani et al , ; Xu et al , ; Derebail et al , ). We and others have reported on the prevalence of CKD as well as the rate of decline in estimated glomerular filtration rate (eGFR) in adults with SCD (Asnani et al , ; Xu et al , ; Derebail et al , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation